Delitos patrimoniales en la alcaldía Cuauhtémoc de la Ciudad de México: un análisis desde la sintaxis espacial (2021)
In recent years, the concerns to identify the variables associated with the occurrence of crimes in specific areas of cities has become more relevant, which has led to the generation of various explanatory frameworks. Some of these state that the cause of crime concentration are socioeconomic factors, while other frameworks attribute this phenomenon to the properties of spatial design. Within this last category, we can find the spatial syntax approach which, in the case of crime, explains how certain variables can influence the spatial behavior of crime. This paper identifies the relationship of spatial properties, such as connectivity and accessibility, and the type of property crime committed in the Cuauhtémoc district of Mexico City. For the analysis, we applied spatial syntax and a zero-inflated negative binomial regression models.